The preparation and characterization of tin sulphide thin film homojunctions - 235319 Samsudi Sakrani; Aznora Aini Isnin; Regional Conference on Solid State Science (16th : 1999 : Penang) (Skudai : Universiti Teknologi Malaysia, 1999)
40